Application of Chitosan From Waste Gurami Fish Scales (Osphronemus goramy) and Clove Powder (Syzygium aromaticum) As Edible Coating on Chicken Meat - Inasabrilla Hendar Dahayu; Djalal Rosyidi (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2021)
Chicken meat is a nutritious food that can increase immunity but has perishable food properties that are easily damaged so it is necessary to add preservatives, namely chitosan as an edible coating to protect the meat from microbial contamination. Gourami (Osphronemus goramy) scales have the potential to be processed as chitosan. Through 3 stages, namely deproteination, demineralization, and deacetylation. The purpose of this study was to determine the effect of adding chitosan with gourami fish scales and cloves as an edible coating on the quality of raw chicken meat at room temperature for 9 h. This study used a factorial completely randomized design (3×3), with factor A: concentration of chitosan solution (0%, 1%, and 2%) and factor B: concentration of clove solution (0%, 1%, and 2%) and repeated 3 times. The results showed that the control treatment without clove and chitosan after 9 h of storage at room temperature had a significant difference in effect on the treated samples. The best treatment was found in the interaction of 2% chitosan (K2) and 2% cloves (C2) with microbial contamination of 2×10 5 CFU/g so that it still meets the standards of the National Standardization Agency (BSN) namely, chicken meat has a maximum requirement of 1×106 CFU/g, which can maintain the quality of meat, both in terms of pH, water content, and acceptability of organoleptic values which are still favored by panelists.